Analisis Prasangka dan Diskriminasi pada Etnis Tionghoa di Indonesia - Hidayat, Muslim; Putra, Megantara; Saputro, Muhammad Rizki; Husna, Rahmawati Nuril (Prodi Studi Agama-Agama, 2023)
Ethnic diversity becomes an advantage for Indonesia, both from the island, race, ethnicity, language, and so on. This diversity can be a selling point in its own international arena. But on the other hand, it also has a negative side. One of the downsides is that it tends to be easy to arise prejudice and discrimination. Prejudice and discrimination itself occur in several groups, one of which is ethnic Chinese. Whereas Indonesia has the motto